A Note on the Topological Sense of Chemical Sets - GOK, OMER; KARAHAN, MESUT (Asian Journal of Chemistry, 2010)
The present studies suggested the way to evaluate some topological properties, such as; closure, derived set, boundary, interior, exterior, semi-openness, semi-closednes, semiregularity, θ-semi closure, θ-semi openness, regular opennes of subsets of chemical set interested in the chemical set chosen at the beginning as object in the work of Restrepo et.al.